Hemitrichia schnittleri and Trichia novozhilovii, two new species of bright-spored myxomycetes from Mongolia - Vlasenko, Anastasia V.; Enkhtuya, Ochirbat; Chelobanov, Boris P.; Vlasenko, Vyacheslav A. (Phytotaxa, 2025)
Two new species of myxomycetes are described in the genera Hemitrichia and Trichia. Each species is given a full description, along with details of ecology and distribution. They are compared to morphologically similar species, using both light and scanning electron microscopy. DNA extracted from the 18S nrDNA regions (SSU), confirmed the two new species.